CAREER-GUIDANCE AND DIGITALIZATION AS LINKS OF ONE PROBLEM - V. Lukin (Publishing House of the State University of Management, 2018)
The methods of work on professional information distribution, professional enlightenment, professional selection, professional education, professional social adaptation are revealed. Within the conditions of worldwide transition to digital economy the reevaluation of socio-economic situations occurs which has an eect on education sector, its relation to society, labour market, culture, a human being and, as a result, economic, moral, spiritual potential of society and civilization as a whole. The value system of the choice of the place of work and study by individuals, the motives for the choice of professional activity are specied.